The durability of building materials under a changing climate. (19th May 2016) - Phillipson, Mark C.; Emmanuel, Rohinton; Baker, Paul H
Abstract : Weathering of materials leads to degradation of the fabric of buildings which if left unchecked will lead to an increase in the rate, and possibly severity, of degradation. Adjustments to maintenance regimes could accommodate marginal changes to degradation rate. However, for significant increases in degradation rate, adaptations may be required. Globally, any new deterioration mechanisms are unlikely. However, in the future previously insignificant problems may start to become significant at a local level, for which there is a lack of local knowledge or experience. Adaptation in the context of existing buildings is a means to further protect the existing fabric, to consolidate performance and control the rate of deterioration. This adaptation goes beyond the scope of enhanced maintenance. For historic buildings, there will be tension between the need to conserve the building and simultaneously adapt in the face of increased climate change driven weathering. Impact studies are needed to identify priorities for adaptation by identifying the scale and impact of degradation‐related defects for the future building stock. Such studies need to be integrated with authoritative information on projected future climate. Adaptation of building design is needed to ensure new buildings consider performance in both current and future climates. A whole‐life approach to building design is needed. To achieve this building standards, building codes need to be developed which consider future climate design. Traditional vernacular styles may offer an opportunity for learning design lessons and adapting design practices that could help facilitate appropriate climate protection. WIREs Clim Change 2016, 7:590–599. doi: 10.1002/wcc.398 This article is categorized under: Assessing Impacts of Climate Change > Evaluating Future Impacts of Climate Change